Nutritional status of children in Central Sulawesi post-earthquake and tsunami: A study based on e-PPGBM data - Mujayanto Mujayanto; Fahmi Hafid (AcTion: Aceh Nutrition Journal, 2024)
The earthquake and tsunami on September 28, 2018, in Central Sulawesi had a severe impact on children's health and nutrition, particularly concerning malnutrition and micronutrient deficiencies. This study compared the nutritional status of children in disaster-affected and unaffected areas. This study employed a cross-sectional design to assess changes in the prevalence of stunting, underweight, and wasting among children aged 6-23 months in Sigi Regency using data from the e-PPGBM System. The study analyzed data from three periods: before and after the disaster, with data from 10,894 children and 10,894 children. Statistical tests were used to identify changes in stunting, underweight, and wasting. The results showed that after the disaster, the average Z-scores of Height-for-Age (HAZ) and Weight-for-Height (WHZ) was significantly lower in the disaster-affected areas than in the unaffected areas (p = 0,00), indicating a sustainable impact on the growth and nutritional status of children. The conclusion of this study shows a significant decline in children's nutritional status in disaster-affected areas compared with unaffected areas. Prompt action and sustained recovery efforts are crucial to address the long-term impacts on children's growth and nutrition